Mining History in the Black Hawk Mining District, Burro Mountains, Southwestern New Mexico - SME Annual Meeting 2025 - Virginia T. McLemore (Society for Mining, Metallurgy & Exploration, 2025)
The Black Hawk district in New Mexico hosts an unusual type of deposit: arsenide five-element veins. These deposits are Ag-Co-Ni-Bi-As-bearing carbonate veins with local concentrations of U, Pb, Zn, Sb, and other elements. They are high-grade silver deposits (1000s g/t Ag), but low tonnage (<1 Mt) and difficult to find. By 1881, claims were staked and a town developed. It is estimated that >$1,500,000 was produced in 1883–1893, when Ag prices dropped due to the 1893 Ag panic. Solid Silver Mining Co. produced $600,000 from the Black Hawk mine; one car load contained $28,000 worth of silver! The town of Black Hawk grew to 125 population by November 1883. By the end of 1893, the town was vacant; nothing remains. The district was idle until 1916, and the mines operated sporadically since because of lack of available capital, water issues, and difficulty in finding ore shoots. The area is a favorite for mineral collectors. Tungsten was found in the district in 1935 in quartz veins associated with pegmatites. Metal production from 1881–1960 is estimated as 3,000 lbs Cu, 1,000 oz Au, 1,286,000 oz Ag, and 4,000 lbs Pb. In addition, 10,542 short tons of 2.7–71% WO ore and 615 short tons of fluorspar ore have been produced from the district.